Skilled riders manage horse gait complexity through a gait transition whilst also maintaining stable horse-rider coordination variability - Wilkins, C. A.; Mulloy, F. (ISBS Proceedings Archive (Michigan), 2023)
Equestrian riders aim to cue smooth transitions between horse gaits. This study aimed to investigate whether competitive horse rider (n=10) decrease horse gait regularity and increase horse-rider coordination variability in the region of a gait transition (n=6; both walk-trot, and trot-canter) relative to baseline walk, trot and canter. Resultant accelerations from IMUs affixed to the horse`s girth and rider`s pelvis were calculated. Horse gait regularity was quantified as multiscale sample entropy (MSSE) of the pelvis. Horse-rider coordination variability (Coordvar) was quantified as the standard deviation of the horse-rider continuous relative phase. Pre-transition MSSE did not increase; post-transition MSSE significantly decreased (paired t-tests; pvar were found. Therefore, horse gait or horse-rider Coord_var does not increase in a transition.